PENGENALAN OLAHRAGA PANAHAN UNTUK SISWA SEKOLAH DASAR ABDURAHMAN BIN AUF - Andi Irfan; Andi Alim; Asriani Minarti S (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2022)
Archery is a sport that is recommended in Islam and sunnah by the prophet Muhammad Sallallahu 'alaihi wasallam. This sport has long been known in Indonesia. By doing archery activities, we can train strength, endurance, focus, hand and eye coordination, balance and increase patience in building self-confidence. The problem that occurs in elementary school students Abdurrahman Bin Auf is that archery is still less well known and also still less attractive because archery is not yet like badminton, futsal, or other sports. Students also do not know the sport of archery and the benefits of doing this sport regularly. The lack of introduction to archery from sports tournaments or services related to archery is also a problem. The PKM activities were carried out by the service team using the lecture, demonstration and practice methods, besides that, an archery competition simulation was also held. The result of this service is the increase in community knowledge and skills about archery, in addition to increasing knowledge of facilities and infrastructure will have an impact on increasing interest in sports, especially in the field of archery.